Quality Measurement of Accurate-5 Accounting Software Using the Iso 9126 Model: Study on Accurate Workshop for D3 Computerized Accounting STMIK Mardira Students - Hasanah Tisna Amijaya; Ramlan Ramlan; Ganjar N Fajar (Jurnal Computech & Bisnis (e-Journal), 2023)
This study aims to evaluate the degree of excellence of the Accurate-5 accounting software by employing the ISO-9126 model, which assesses six dimensions (primary characteristics) and associated attributes (secondary characteristics) of software quality. The researchers measured a sample of 41 participants who attended a workshop at STMIK Mardira Indonesia Bandung using the Accurate-5 software. The researchers gathered primary data using a questionnaire that utilized the Likert scale. The validity test results supported the validity of the items, as a value greater than 0.316 was found. The reliability test results demonstrated that all attributes have a high level of reliability, as each item had a Cronbach's alpha value greater than 0.7. The software quality evaluation findings utilizing the ISO 9126 standard indicate that all dimensions and attributes satisfy the "Good" criteria. The researchers found that the attributes of Compliance, Installability, and Coexistence satisfy the criteria of "Very Good." Based on the data, we can infer that the Accurate-5 software complies with the ISO 9126 standard as it achieved an average percentage score of 77.53%, indicating that it meets the "Good" criteria.